Partial Recovery of Audiological, Vestibular, and Radiological Findings following Spontaneous Intralabyrinthine Haemorrhage. (24th December 2013) - Pézier, Thomas; Baráth, Krisztina; Hegemann, Stefan
Abstract : The diagnosis, work-up, and treatment of sudden sensorineural hearing loss and sudden vestibular loss vary widely between units. With the increasing access to both magnetic resonance imaging and objective vestibular testing, our understanding of the various aetiologies at hand is increasing. Despite this, the therapeutic options are limited and without a particularly strong evidence base. We present a rare, yet increasingly diagnosed, case of intralabyrinthine haemorrhage (ILH) together with radiological, audiological, and vestibular test results. Of note, this occurred spontaneously and has shown partial recovery in all the mentioned modalities.